THE FALAK SCIENCE OBSERVATORY OF UNIVERSITY OF MUHAMMADIYAH NORTH SUMATRA (OIF UMSU) AND THE CONTRIBUTION IN FAJR TIME RESEARCH - Arwin Juli Rakhmadi; Abu Yazid Raisal; Muhammad Hidayat; Hariyadi Putraga; Isra Hayati (Proceeding International Seminar of Islamic Studies, 2021)
The Falak Science Observatory of the University of Muhammadiyah North Sumatra (abbreviated OIF UMSU) is an observatory that is engaged in the study and research of Islamic Astronomy. Structurally, this institution is under the auspices of the University of Muhammadiyah North Sumatra (UMSU). One focus of The Falak Science Observatory of the University of Muhammadiyah North Sumatra is the fajr time (true dawn) research by using Sky Quality Meter (SQM) instruments. OIF UMSU's Fajr time research data has compiled up to hundred data (days), collected from 2017 to 2020. Besides, some of OIF UMSUs data also been utilized by various parties in the research and development of the dawn study and Falak science in general. This article will present at a glance about OIF UMSU and the contribution to Fajr Time research using Sky Quality Meter.